(untitled) (Advancements in Homeopathic Research, 2023)
A ganglion cyst is soft tissue swelling that occurs most commonly over the wrist and hand. Apart from bumps, many ganglion cysts are asymptomatic. Sometimes pain, weakness, or paraesthesia may present. The two main concerns for patients have been the cosmetic appearance of the cysts and the fear of future malignant growth. Current treatment of ganglion cysts has only options- either conservative or surgical excision. But there is a change of reappearance of development even after successful surgical intervention. In homeopathy, there is ample literature regarding ganglion cysts and encouraging documents regarding the treatment of ganglion cysts. Below the present case report intends to record individualized homoeopathic constitutional medicine that cured a ganglion cyst on the wrist. Drug selection is exclusively based on the totality of symptoms. But the present case report is based on a single case; it required more extensive research and clinical studies to improve the study outcome. [1]